THE ROLE OF THE NATIONAL GIS FOR THE OWNERSHIP OF THE LAND PROPERTIES: THE ROLE OF THE NATIONAL GIS FOR THE OWNERSHIP OF THE LAND PROPERTIES - Ivanova , Ilinka (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The creation, storage and transmission of data from the plans and maps and property records to them, used for the development of general and detailed plans is granted to various institutions. This raises serious inconvenience and problems relating to the guarantee of the natural and legal persons’ property in the investment design, real estate trade, territory planning etc. The establishment of a National Geographic Information System, which combines created in Bulgaria maps and plans which serve in the investment planning and spatial planning will ensure the ownership and will end many litigations, which have not only tangible but also intangible consequences.